Knee extensor disruption in mild diplegic cerebral palsy: a risk for adolescent athletes. (20th February 2013) - Elhassan, Yahya; O'Sullivan, Rory; Walsh, Mike; O Brien, Tim
Abstract : We report three cases of adolescent boys with mild diplegic cerebral palsy (CP) who suffered disruption of the knee extensor mechanism. Two had fractures of the patella and the third a fracture avulsion of the tibial tubercle combined with an undisplaced fracture of the patella. All three had gait analysis prior to sustaining the fractures and were known to have mild knee crouch. Each participated in sport including football. Each suffered an acute deterioration in gait resulting in a referral for repeat gait analysis, and x-ray of the affected knee. With the increased involvement of children with CP in sporting activities, especially children with mild knee crouch, we caution that knee extensor rupture might be an increasing problem.